Young Age at Diagnosis of Type 1 Diabetes Is Associated with the Development of Celiac Disease-Associated Antibodies in Children Living in Newfoundland and Labrador, Canada - Harpreet Pall; Leigh A. Newhook; Hillary Aaron; Joseph Curtis; Ed Randell (MDPI AG, 2015)
Objectives: The objectives of this study were to establish the prevalence of positive antibodies to endomysium (EMA) and tissue transglutaminase (tTG) in children with type 1 diabetes living in Newfoundland and Labrador (NL), and to examine clinical features associated with positive antibodies. Methods: Patients were recruited from the pediatric diabetes clinic. One hundred sixty-seven children with type 1 diabetes from the 280 children followed at the clinic were prospectively screened for celiac disease using EMA and tTG. The variables of Irish descent, age at onset of diabetes, duration of diabetes, sex, family history of celiac disease, hemoglobin A1C (A1C), ferritin, gastrointestinal symptoms, and body mass index were compiled for all patients. The group of patients with positive antibodies to EMA and/or tTG was compared to the group with negative antibodies. Results: The prevalence of patients with positive antibodies to EMA and/or tTG was 16.8% (n = 28). One patient had also been previously diagnosed with symptomatic celiac disease. The two statistically significant variables with positive antibodies were an earlier age at onset of diabetes (Mann-Whitney U two-tailed test: mean difference 3.2 years, 95% CI 1.7-4.8 years, p < 0.0001) and longer duration of diabetes (Mann-Whitney U two-tailed test: mean difference 2.9 years, 95% CI 1.3-4.4 years, p < 0.0001). Irish descent was associated with positive antibodies but did not reach statistical significance. On logistic regression analysis performed with these three variables together, only age at onset of diabetes remained significant. Conclusions: There is a high prevalence of celiac disease-associated antibodies in children living in NL with type 1 diabetes. Unlike other clinical features, an earlier age at onset of diabetes was predictive for positive antibodies. As the majority of children with positive antibodies did not have signs or symptoms of celiac disease, routine screening for celiac disease in type 1 diabetes is recommended.